Pipelines 2018. proceedings of sessions of the Pipelines 2018 Conference, July 15-18, 2018, Toronto, Ontario, Canada - Macey, Christopher C.; Lueke, Jason, S. (American Society of Civil Engineers, 2018)
"This collection contains 46 peer-review papers on the planning and design of pipeline systems. Topics include: pipeline installation in constrained locations; design considerations for water supply; planning and alternative delivery methods; design-build for pipelines; and international case studies."--